2004
DOI: 10.1126/science.1100021
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Overactivity Impairs Prefrontal Cortical Regulation of Working Memory

Abstract: The prefrontal cortex is a higher brain region that regulates thought, behavior, and emotion using representational knowledge, operations often referred to as working memory. We tested the influence of protein kinase C (PKC) intracellular signaling on prefrontal cortical cognitive function and showed that high levels of PKC activity in prefrontal cortex, as seen for example during stress exposure, markedly impair behavioral and electrophysiological measures of working memory. These data suggest that excessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
267
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(292 citation statements)
references
References 17 publications
13
267
2
6
Order By: Relevance
“…As reported in previous studies, brain NE system activation may stimulate arousal and contribute to execution of goal oriented actions (Frazer, 2000;Aston-Jones et al, 1991). On the other hand, NE has an inverted U-shaped influence on these behavioral outcomes (Birnbaum et al, 2004). Hence, it is possible that if the NE system is excessively stimulated, as for example in the mPFC, it may mediate disruption of these behaviors.…”
Section: Discussionmentioning
confidence: 91%
“…As reported in previous studies, brain NE system activation may stimulate arousal and contribute to execution of goal oriented actions (Frazer, 2000;Aston-Jones et al, 1991). On the other hand, NE has an inverted U-shaped influence on these behavioral outcomes (Birnbaum et al, 2004). Hence, it is possible that if the NE system is excessively stimulated, as for example in the mPFC, it may mediate disruption of these behaviors.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, DAG metabolism, which is highly aberrant in diseased PFC, has been implicated in a number of synaptic processes including the regulation of dendritic spine morphology, plasticity, and neurotransmitter release (37). Importantly, overactivation of PKC, a target of DAG, interferes with PFC-regulated working memory (38), a key feature of AD. DAG accumulation in the PFC likely occurs through A␤-stimulated hydrolysis of PI(4,5)P 2 by PLC (10), based on the specific accumulation of polyunsaturated DAG 38:4 (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Birnbaum and associates 198 demonstrated that excessive activation of PKC (including by stress)…”
Section: Protein Kinase C Signaling Cascade: a Shared Biochemical Tarmentioning
confidence: 99%